Unified state boundary surface model for clay and sand under saturated and unsaturated conditions - Chortham Srinil; Veerayut Komolvilas; Mamoru Kikumoto (Soils and Foundations, 2022)
A unified state boundary surface that defines the upper limit of the specific volume of saturated clay and sand is first derived. It is extended to unsaturated soils by applying Bishop’s effective stress and using the effective degree of saturation as an independent state variable. Then, a critical state model for unsaturated clay and sand is formulated based on the unified state boundary surface. The model combines a rational soil–water characteristic curve incorporating packing density and hydraulic hysteresis. The model is validated by comparing the calculated results and results of extensive experiments, including one-dimensional and isotropic compression tests, triaxial shearing tests, and soaking-collapse tests under isotropic and anisotropic stress conditions on sand, clay, and mixed soil under saturated and unsaturated conditions. The proposed unified soil model presents a noble and universal framework for the rational description of broad soils’ behavior, in which the state boundary surface plays a central role. The model accurately predicts the compression, shearing, and soaking-induced collapse behaviors of various soil types in saturated and unsaturated conditions.